THE DATA AND KNOWLEDGE BASE FOR PROJECT PLANNING OF PLANT PROTECTION BY SPRAYING - БОЯРЧУК, Віталій Мефодійович; ШОЛУДЬКО, Петро Васильович; МИХАЛЮК, Микола Адамович; ТРИГУБА, Інна Леонтіївна (Vìsnik NTU <<HPÌ>>. Serìâ: Strategìčne upravlìnnâ, upravlìnnâ portfelâmi, programami ta proektami (Online), 2015)
The peculiarities of the project planning of plant protection by spraying have been presented. The reason and consequences relations among elements of the environment of plant protection project by spraying have been grounded. The mutual relations among process planning of the plant protection project by spraying have been considered and the data and knowledge base for these projects planning have been presented.